Effect of Concentration of Mango Seed Extract (Mangifera Indica L.) as an Organic Inhibitor on Iron Nail Corrosion in NaCl Solution Medium - Almahdali, Khafifah; Walanda, Daud K; Napitupulu, Mery (Universitas Tadulako, 2019)
This study aims to determine the effect of mango seed extract concentration on the rate of corrosion of iron nails in corrosive medium of NaCl solution and seawater as comparison.The research begins with maceration of mango seeds followed by evaporation to produce the extract as an inhibitor with a variation of concentration 1 - 5%. The method of determining the corrosion rate was the weight loss method with soaking for 7 days. The results showed that the highest corrosion inhibition efficiency occurred at 3% concentration for immersion with corrosive medium of 3% NaCl and 2% concentration for soaking in sea water with efficiency respectively 15.34% and 10.63%. Based on the results of the study, it was found that the increasing concentration of mango seed extract resulted in the efficiency effect on corrosion of nails.